2022
DOI: 10.3390/su141710749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Countermeasures of High-Quality Development of China’s Marine Economy Based on PSO-SVM

Abstract: An accurate grasp of the high-quality development of the marine economy is important for the timely adjustment of marine policies and the promotion of sustainable development of the ocean. Based on the latest development philosophy, this paper constructed the evaluation index system of high-quality development of marine economy from five dimensions including innovation, coordination, green, openness, and sharing. The particle swarm optimization (PSO) algorithm and support vector machine (SVM) model based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In the aforementioned research, this paper measured and analyzed China's highquality development of the marine economy from different perspectives, including the national, regional, and provincial levels. Overall, the level of China's high-quality development of the marine economy shows a steady upward trend, which is consistent with the conclusions of some scholars [6,9,14]. The reasons for this can be attributed, on the one hand, to the increasing attention given to marine economic development by the country since 2008.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the aforementioned research, this paper measured and analyzed China's highquality development of the marine economy from different perspectives, including the national, regional, and provincial levels. Overall, the level of China's high-quality development of the marine economy shows a steady upward trend, which is consistent with the conclusions of some scholars [6,9,14]. The reasons for this can be attributed, on the one hand, to the increasing attention given to marine economic development by the country since 2008.…”
Section: Discussionsupporting
confidence: 88%
“…These studies have revealed significant disparities in the level of high-quality development of the marine economy among coastal regions. Scholars have also explored paths for achieving high-quality development from various perspectives, including ecological environmental protection [11], national security strategies [12], building a modern marine industry system [13,14], optimizing spatial layout [15], and enhancing efficiency through factors such as technology [16], funds [17], and policies [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it supports the construction of a comprehensive indicator system to evaluate the quality of economic development. For instance, Gao et al (2022) proposed an evaluation index system that includes perspectives on the marine economy, resources, and environment. Their findings showed steady improvements in Jiangsu's HQMED.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike other evaluation systems guided by the “Five Development Concepts” [ 45 , 46 ], this study combines the perspective of ecological niche theory with the actual resources on which the development of watershed cities is based, and constructs a reasonable index system, which makes the research results more relevant to reality and the path selection more scientific and reasonable. Most of the previous research studies only focused on the evaluation of the high-quality development level [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%